Hiding behind a mask: A multilevel perspective of burnout shame - Ferreira, A. I. (Burnout while working: Lessons from pandemic and beyond, 2022)
The Covid-19 pandemic brought new challenges for employees and employers all over the world. Drawn upon the JD-R model, a multilevel approach is conceptualised where the reduced resources (e.g., social support) and increased demands imposed by the pandemic (e.g., work/home spillover, social distancing, adoption of remote work and new technologies), improved the frequency of burnout. The framework of conservation of resources theory (COR) is adopted to explain that the lack of resources brought by demands to acquire and protect employee's resources during the pandemic (e.g., job security, well-being) exacerbated burnout behaviour and under certain circumstances allowed employees to hide their burnout symptoms. Moreover, the lack of social support, cultures and climates of presenteeism, and perceptions of stigmatisation that health problems are not culturally valued in the workplace, moderate at different levels the role of burnout in explaining the burnout shame phenomenon. In the current study the model presented is conceptualised as a dynamic spiral where higher levels of burnout shame lead people to hide and seek fewer resources (e.g., social support), which in turn tends to boost burnout levels and consequently, reduce the levels of well-being and job performance.